Total knee arthroplasty at Gaza Strip Palestine: compliance and retrospective comparative study - Afana, Hatem B.; Dhair, Rafat F. (International Journal of Research in Orthopaedics, 2019)
Background: In Gaza Strip, arthroplasty only performed at our center. This study is to assess the compliance and improve current practices. Methods: Study is based on medical records review of all patients underwent total knee arthroplasty (TKA) between January 2016 and December 2017. Results: Forty eight TKA were performed on 41 patients. Neuraxial anesthesia used in 43 operations (30 spinal, 13 epidural). Tranexamic acid used in 20 operations and those show less frequently decrease in hemoglobin level after surgery and for blood transfusion. Simultaneous bilateral TKA used in one patient. Drain used in 26 operations, 2 of them had infection. No one started physiotherapy at same day surgery, this may be due to repeat doses of Epidural anesthesia, performed surgeries before weekend and using the drain. Delayed physiotherapy is associated with prolong hospitalization and increase suspicion of deep venous tthrombosis. The result from our retrospective comparative study was similar to guidelines. Conclusions: We concluded that there is overall good management of TKA in our hospital according to the best available evidence. We recommend to use the international guidelines like the American Academy of Orthopaedic Surgeons (AAOS) guidelines as a standard guidelines to our Hospital, and increase awareness of our staff to the good practice guidelines. Emphasize the important elements that we have shorten of good practice as listed in the discussion.